Pendampingan Kelompok Usaha Kerajinan Bambu Untuk Peningkatan Produktivitas UMKM Di Desa Pehkulon Kabupaten Kediri - Fauziyah Fauziyah; Prima Noermaning Attarie; Fatimah Nursandi; Untung Santoso; Wahyuni Sri Astutik (STIE Malangkucecwara, 2023)
Bamboo as a natural resource must be utilized as well as possible and its existence is maintained so that it does not run out. Bamboo products actually have a high aesthetic value. If bamboo is transformed into a beautiful craft, it will add high economic value and is a bright industrial prospect. In addition, bamboo material does not damage the environment, so it helps to protect nature and reduce theoccurrence of Global Warning. Consumers will be more observant in choosingenvironmentally friendly products. The existence of Bamboo Craftsmen in PehkulonVillage grows slowly and their products are considered unattractive in thecommunity. This is because many craftsmen have switched professions, besides thelack of production tools owned by bamboo craftsmen. So far, craftsmen makebamboo crafts using only very simple tools, namely knives and machetes. Besidesthat, craftsmen do not understand management science, such as financialmanagement, production management, marketing management, accounting andhave never received entrepreneurship coaching and training. Prior to communityservice activities, the products produced by the bamboo craft business group wereo nly bamboo fences and woven bamboo. After carrying out community service activities, now the bamboo craftsman business group has been able to make various product diversification and innovations such as: bamboo decorative lights, bamboo lap top cases, bamboo keyboards, bamboo mice, bamboo furniture, bamboo fountains, bamboo decorations, etc. With mentoring, training, discussion and participatory activities, bamboo craft business groups can produce varied products and innovations so that they can compete and increase people's income